Ways of improving hygienic conditions in patients with mandibular fractures - Idashkina, N.; Aliakhbar, M. (Actual Dentistry, 2018)
Purpose: improving the effectiveness of treatment in patients with mandibular fractures. Methods. The study is based on the analysis of the treatment results of 30 patients with mandibular fractures within the dental arch, which were treated by the developed splintage technique using bracket technology and controlled fragments repositioning and using the drug «Tantum Verde®». Results. Patients with mandibular fractures after injury have considerably worsened oral hygiene. Subsequently, the used splint for treatment creates local conditions for the violation of self-cleaning processes and the formation of dental plaque in patients with mandibular fractures. The microflora of dental plaque changes dynamically throughout the treatment period. Originally formed plaque contains aerobic microorganisms, more mature – aerobic and anaerobic bacteria. In the event of significant changes in the immune system and against the background of immunosuppression (both as a result of stress associated with the injury and sometimes as a result of general antibiotic therapy), Candida albicans increases significantly for 3 weeks. Conclusions. A pathogenetically-based drag for prevent cavity in patients with mandibular fractures is «Tantum Verde®» – NSAID with antimicrobial and analgesic action. Key words: mandibular fractures, splints, brackets, oral hygiene, «Tantum Verde®».